Oligonucleotide therapies for nonalcoholic steatohepatitis - Sixu Li; Feng Xiong; Songbo Zhang; Jinghua Liu; Guangping Gao; Jun Xie; Yi Wang (Elsevier, 2024)
Nonalcoholic steatohepatitis (NASH) represents a severe disease subtype of nonalcoholic fatty liver disease (NAFLD) that is thought to be highly associated with systemic metabolic abnormalities. It is characterized by a series of substantial liver damage, including hepatocellular steatosis, inflammation, and fibrosis. The end stage of NASH, in some cases, may result in cirrhosis and hepatocellular carcinoma (HCC). Nowadays a large number of investigations are actively under way to test various therapeutic strategies, including emerging oligonucleotide drugs (e.g., antisense oligonucleotide, small interfering RNA, microRNA, mimic/inhibitor RNA, and small activating RNA) that have shown high potential in treating this fatal liver disease. This article systematically reviews the pathogenesis of NASH/NAFLD, the promising druggable targets proven by current studies in chemical compounds or biological drug development, and the feasibility and limitations of oligonucleotide-based therapeutic approaches under clinical or pre-clinical studies.